Iain Provan, V. Philips Long & Tremper Longman III. A biblical history of Israel. Louisville, Westminster: John Knox Press, 2003, XIV, 426 pp. - Pfoh, Emanuel (Estudios de Asia y África, 2007)
Iain Provan, V. Philips Long & Tremper Longman III. A biblical history of Israel. Louisville, Westminster: John Knox Press, 2003, XIV, 426 pp.